How Do Oral Medications, Botulinum Toxin Use, and Treatment Burden Change after Deep Brain Stimulation for Dystonia? - Hikaru Kamo; Emma Leone; Rohini Kumar; Chase Antilla; Isabelle Gerzenshtein; Arunmozhimaran Elavarasi; Aparna Wagle Shukla (Movement Disorders Clinical Practice, 2026)
Abstract Background Deep brain stimulation (DBS) is an established therapy for dystonia; however, the long‐term trajectory of adjunctive treatment burden, including oral medications and botulinum toxin (BoNT) injections, and the likelihood of achieving medication‐free status remain poorly understood, despite important implications for adverse effects, injection burden, and quality of life. Objective Determine long‐term changes in adjunctive medication burden and the durability of medication‐free status among dystonia patients undergoing DBS. Methods We retrospectively examined the proportion of dystonia patients requiring oral medications and BoNT therapy after DBS, tracking postoperative changes at 6 months, 1, 3, 5, and 10 years. Factors influencing overall medication burden were evaluated, and the proportion of patients achieving treatment‐free status was determined. Results Among 100 patients in this cohort (56% generalized dystonia), baseline use of oral medications and BoNT was 85% and 43%, respectively. The proportion requiring oral medications and BoNT declined to ~60% and ~ 20–25% as DBS benefits emerged, with reductions maintained throughout follow‐up. Among those continuing BoNT, dosing remained largely unchanged. The overall medication burden score, calculated by combining oral medications and BoNT, was significantly reduced at all follow‐up intervals, with body distribution influencing the magnitude of reduction. Around one‐third of patients did not require any medications at 10‐year follow‐up. Conclusion DBS leads to sustained reductions in adjunctive oral medications and BoNT use. At 10‐year follow‐up, around 20% of dystonia patients continued to require BoNT injections, but 30% were completely medication‐free. These data highlight evolving long‐term benefits and inform patient expectations.